Free Lipase‐Catalyzed Esterification of Oleic Acid for Fatty Acid Ethyl Ester Preparation with Response Surface Optimization. (28th September 2012) - Ren, Hongjie; Li, Yang; Du, Wei; Liu, Dehua
Abstract: Free lipase‐mediated alcoholysis for biodiesel production has drawn increasing attention in recent years due to its advantages of lower cost and faster reaction rate compared to immobilized lipase. Ethanol, derived from renewable biomass, has a great potential for biodiesel production. A previous study showed that free lipase NS81006 could effectively catalyze the ethanolysis of triglycerides for biodiesel preparation. Since most crude plant oils always contain an amount of free fatty acids, oleic acid was used as the model substrate for this study on lipase‐mediated esterification for biodiesel production. The central composite design of the response surface methodology was adopted for process optimization. A biodiesel yield of over 90 % was achieved under optimal reaction conditions and the repeated use of the free lipase was easily realized through phase separation either by natural gravity force or centrifugation.